Pengaruh Kualitas Layanan, Citra Perusahaan Dan Penanganan Keluhan Terhadap Loyalitas Dengan Kepuasan Sebagai Intervening Pada Nasabah Bank NTT Cabang Maumere - Odang, Laura Maria Jeanne; Yohanes Mbani (Jurnal Projemen UNIPA, 2026)
This study aims to test and analyze the effect of service quality, corporate image and complaint handling on satisfaction. As well as to test and analyze Service Quality on Loyalty with Satisfaction as Intervening for Customers of Bank NTT Maumere Branch. This research is a type of explanatory research with a quantitative approach. The sample population is 220 customers of Bank NTT Maumere Branch. The sampling technique in this study was purposive sampling. The data analysis technique uses the Partial Least Square (PLS) approach with variance based SEM using PLS 4.01 smart tools. The results of the analysis can be concluded that Service Quality, Corporate Image and Complaint Handling have a significant effect on Customer Satisfaction of Bank NTT Maumere Branch; and Satisfaction has a significant effect on Customer Loyalty; and Service Quality, Corporate Image and Complaint Handling have a significant effect on Customer Loyalty through Customer Satisfaction of Bank NTT Maumere Branch.